UNDERSTANDING OBLIQUE IMPACTS FROM EXPERIMENTS, OBSERVATIONS, AND MODELING - Pierazzo E.; Melosh H.J. (My University, 2000)
Natural impacts in which the projectile strikes the target vertically are virtually nonexistent. Nevertheless, our inherent drive to simplify nature often causes us to suppose most impacts are nearly vertical. Recent theoretical, observational, and experimental work is improving this situation, but even with the current wealth of studies on impact cratering, the effect of impact angle on the final crater is not well understood. Although craters' rims may appear circular down to low impact angles, the distribution of ejecta around the crater is more sensitive to the angle of impact and currently serves as the best guide to obliquity of impacts. Experimental studies established that crater dimensions depend only on the vertical component of the impact velocity. The shock wave generated by the impact weakens with decreasing impact angle. As a result, melting and vaporization depend on impact angle; however, these processes do not seem to depend on the vertical component of the velocity alone. Finally, obliquity influences the fate of the projectile: in particular, the amount and velocity of ricochet are a strong function of impact angle.